Linear polarization of BL Lacertae OJ287 at 21 cm - Xavier, Carlton (fi=Turun yliopisto|en=University of Turku|, 2017)
This thesis presents the calculation and analysis of the linear polarization Stokes parameters for the BL Lacertae OJ287. OJ287 is one of the best monitored BL Lacs with its optical historic light curve presenting well documented observations for over a hundred years. A binary black hole model by Sillanpää et al. 1988 which was later updated by Lehto and Valtonen 1996 was successful in explaining the majority of the observed phenomenon including the 12 year double optical ﬂaring periodicity. In 2004 a long term radio-optical monitoring period was commenced to study the ﬂaring period between 2005-2008. The author has studied OJ287 using the single dish Nançay Radio telescope in France at the wavelength of 21 cm. A correction pipeline to reduce the excess error in the data is outlined while brieﬂy discussing possible sources contributing to the error. The linear Stokes parameters were calculated and the results analyzed to explore the variability of ﬂux and polarization parameters. The polarized ﬂux increased in September 2007 and remained relatively stable until April 2008 when it started to reduce. The electric vector position angle (EVPA) was relatively stable through out the monitoring period. Correlation analysis was performed between the ﬂux, polarization degree and the position angle. We see a moderate anticorrelation between the ﬂux and polarization degree which can be explained well using the two component model. The Nançay data was compared to the University of Michigan Radio Observatory (UMRAO) data at 14.5 and 8.0 GHz. No clear common trend was observed between the two data sets. The observed polarization degree in the Nançay data is higher than the values seen at UMRAO frequencies which could be due to certain unaccounted systematic errors.